Investigating the impact of inter-limb asymmetry in hamstring strength on jump, sprint, and strength performance in young athletes: comparing the role of gross force - Jiang, Dongting; Liu, Zijian; Ling, Xiaoyu; Dai, Jinjin; Long, Lijun; Lu, Yongren; Zhou, Shengqing (Frontiers in Physiology, 2023)
The main purpose of this cross-sectional study was to examine the impact of the inter-limb asymmetry of hamstring strength on jump, sprint and strength performance and to compare the effects of inter-limb asymmetry of hamstring strength with gross force (GF) of the hamstring on these physical qualities in youth volleyball athletes. Eighty-one youth volleyball players (age: 16.6 ± 1.9 years; training experience: 3.0 ± 0.9 years; height: 191.4 ± 7.1 cm; body mass: 78.5 ± 12.9 kg; lean body mass: 63.5 ± 10.5 kg; body fat rate: 18.6 ± 6.1 %) performed a mid-season battery of tests consisting of morphological test, depth jump (DJ), counter movement jump (CMJ), squat jump (SJ), 10 m sprint, isometric mid-thigh pull (IMTP) and hamstring strength test. All tests reported good to excellent reliability (ICC range = 0.815 to 0.996) and acceptable variability (CV range = 3.26 to 7.84%). Results show a significant negative relationship between inter-limb asymmetry of hamstring strength and all physical qualities (r= -0.271 to -0.445; p < 0.05), and a significant positive relationship between GF of hamstring and all physical qualities (r= 0.303 to 0.664; p < 0.05). Additionally, GF of hamstring was more relevant to IMTP-PF (peak force) (r= 0.664) and inter-limb asymmetry of hamstring strength was more relevant to 10 m sprint (r= -0.445). The findings from this study indicate that, for youth athletes, the GF of the hamstring is crucial for overall lower limb strength performance, and the importance of inter-limb symmetry of hamstring strength increases with the complexity of the task.